Ethnomathematics Exploration of Eceng Gondok Crafts - Ernaningsih, Zeny; Kristiyani, Ika Murti (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Mathematics is a basic science that is always related to other sciences. Many people think of mathematics as a science requiring more effort. Ethnomathematics, as a scientific study, can bridge the gap between mathematics, culture, and life. Through ethnomathematics, it becomes easier for students to learn mathematics. This paper involves a mathematical exploration of eceng gondok crafts. Eceng gondok is one of the main ingredients for handicrafts in great demand by people at home and abroad. The primary objective of this research is to explore the mathematical elements in eceng gondok crafts. Teachers and students can use the results of this study as a learning medium to facilitate understanding in learning some mathematical material. This research follows qualitative descriptive research with an ethnographic focus. This study used observation and interviews with one of the eceng gondok craft industry owners in collecting data. Data analysis from this research was conducted inductively through four activities: collecting, reducing, categorizing, and drawing conclusions. The results found that this eceng gondok craft contained many mathematical elements, including geometric concepts, calculus concepts, and a system of linear equations in three variables.